Effects of mtDNA in SHR-mtF344 versus SHR conplastic strains on reduced OXPHOS enzyme levels, insulin resistance, cardiac hypertrophy, and systolic dysfunction - Houštěk, Josef; Vrbacký, Marek; Hejzlarová, Kateřina; Zídek, Václav; Landa, Vladimír; Šilhavý, Jan; Šimáková, Miroslava; Mlejnek, Petr; Kazdová, Ludmila; Mikšík, Ivan; Neckář, Jan; Papoušek, František; et al. (Physiological genomics, 2014)
Common inbred strains of the laboratory rat can be divided into four major mitochondrial DNA (mtDNA) haplotype groups represented by the BN, F344, LEW, and SHR strains. In the current study, we investigated the metabolic and hemodynamic effects of the SHR vs. F344 mtDNA by comparing the SHR vs. SHR-mt(F344) conplastic strains that are genetically identical except for their mitochondrial genomes. Altogether 13 amino acid substitutions in protein coding genes, seven single nucleotide polymorphisms in tRNA genes, and 12 single nucleotide changes in rRNA genes were detected in F344 mtDNA compared with SHR mtDNA. Analysis of oxidative phosphorylation system (OXPHOS) in heart left ventricles (LV), muscle, and liver revealed reduced activity and content of several respiratory chain complexes in SHR-mt(F344) conplastic rats compared with the SHR strain. Lower function of OXPHOS in LV of conplastic rats was associated with significantly increased relative ventricular mass and reduced fractional shortening that was independent of blood pressure. In addition, conplastic rats exhibited reduced sensitivity of skeletal muscles to insulin action and impaired glucose tolerance. These results provide evidence that inherited alterations in mitochondrial genome, in the absence of variation in the nuclear genome and other confounding factors, predispose to insulin resistance, cardiac hypertrophy and systolic dysfunction.
Keywords: Gene Dosage; Insulin; potkani inbrední F344; mitochondriální DNA; velikost orgánu; DNA, Mitochondrial; Insulin Resistance; diabetes; sekvence nukleotidů; Electrocardiography; Glucose; haplotypy; fenotyp; Male; funkce levé komory srdeční; inzulinová rezistence; Phenotype; inzulin; mitochondriální geny; RNA transferová; Organ Size; mitochondria; Oxidative Phosphorylation; Sequence Analysis, DNA; heart mass; genová dávka; Genes, Mitochondrial; conplastic; potkani inbrední SHR; sekvenční analýza DNA; molekulární sekvence - údaje; Haplotypes; transport elektronů; glukosa; mužské pohlaví; metabolismus lipidů; adeninnukleotidy; Cardiomegaly; Electron Transport; Animals; krevní tlak; RNA, Transfer; kardiomegalie; zvířata; Lipid Metabolism; Blood Pressure; Rats, Inbred SHR; Glucose Tolerance Test; systola; Systole; Adenine Nucleotides; Molecular Sequence Data; Base Sequence; Rats, Inbred F344; spontaneously hypertensive rat; oxidativní fosforylace; glukózový toleranční test; elektrokardiografie; Ventricular Function, Left